2018
DOI: 10.1002/jpln.201700446
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of macro and micronutrients in blades and petioles of Vitis vinifera L. cv. Mencía and Sousón

Abstract: In the case of grapevine (Vitis vinifera L.), leaf blade and petioles at different sampling times are used for nutritional diagnosis and planning fertilization practices. However, reference values for each nutrient depend on the scion-rootstock combination. In this sense, the current study aimed at determining the reliability of leaf blade and petiole for diagnosis at different phenological stages and, also, of the period of validity, around flowering and veraison, in which the nutrient concentrations obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…Leaf sampling was made from whole leaves (blade+petiol) because it was not possible to obtain enough sample using only petioles from young plants. In addition, Cancela et al (2018) reported that leaf blades would be preferable to petioles for macronutrient detection. After the development of the vine shoots, five, six and seven fully developed mature leaves (Dami and Smith, 2019) were used backwards from the tip of the main shoot in late August and early September.…”
Section: Analysis Of Macronutrients In the Leafmentioning
confidence: 99%
“…Leaf sampling was made from whole leaves (blade+petiol) because it was not possible to obtain enough sample using only petioles from young plants. In addition, Cancela et al (2018) reported that leaf blades would be preferable to petioles for macronutrient detection. After the development of the vine shoots, five, six and seven fully developed mature leaves (Dami and Smith, 2019) were used backwards from the tip of the main shoot in late August and early September.…”
Section: Analysis Of Macronutrients In the Leafmentioning
confidence: 99%